Germination behaviour of 6 × 6 diallel hybrids of an energy crop Jatropha curcas L. - Aminul Islam, A.K.M.; Nurina Anuar,; Zahira Yaakob,; Jaharah A. Ghani, (Universiti Kebangsaan Malaysia, 2015)
The seeds of 6 × 6 half diallel progenies of Jatropha curcas were used to evaluate the effects of genotypes (parents and their hybrids) on germination traits of jatropha at Universiti Kebangsaan Malaysia. Germination traits were varied significantly (p<0.01) among the seeds of hybrids and their parents. The germination was started at four days after planting and prolonged until 15 days. Seed germination varied from 58.06 to 92.76% among the parents and 53.43 to 98.96% among the hybrids. The highest germination was observed in the hybrid P2 × P4 and none of the hybrid or parent showed complete (100%) germination. The maximum GI (germination index) and SVI (seedling vigour index) were found in the hybrids P1 × P5 and P1 × P2 and the lowest in P2 × P4 and P3 × P6, respectively. For most germination parameters parents behaved poorly than that of the hybrids.